Inequality Bands: Seventy-Five Years of Measuring Income Inequality in Latin America - Facundo Alvaredo; Francois Bourguignon; Francisco H. G. Ferreira; Nora Lustig (Institute of Labor Economics (IZA), 2024)
Drawing on a comprehensive compilation of quantile shares and inequality measures for 34 countries, including over 5,600 estimated Gini coefficients, we review the measurement of income inequality in Latin America and the Caribbean over the last seven decades. We find that there is quite a bit of uncertainty regarding inequality levels for the same country/year combinations. Differences in inequality levels estimated from household surveys alone are present but they derive from differences in the construction of the welfare indicator, the unit of analysis, or the treatment of the data. With harmonized household surveys, the discrepancies are quite small. The range, however, expands significantly when –to correct for undercoverage and underreporting especially at the top of the distribution– inequality estimates come from some combination of surveys and administrative tax data. The range increases even further when survey-based income aggregates are scaled to achieve consistency not only with tax registries but with National Accounts. Since no single method to correct for underreporting at the top is fully convincing at present, we are left with (often wide) ranges, or bands, of inequality as our best summaries of inequality levels. Reassuringly, however, the dynamic patterns are generally robust across the bands. Although the evidence roughly until the 1970s is too fragmentary and difficult to compare, clearer patterns emerge for the last fifty years. The main feature is a broad inverted U curve, with inequality rising in most countries prior to and often during the 1990s, and falling during the early 21st century, at least until around 2015, when trends appear to diverge across countries. This pattern is broadly robust but features considerable variation in timing and magnitude depending on the country.
Keywords: D31; D63; O54; 330; income inequality; measurement; Latin America and the Caribbean